Comparison of two different microsurgical methods in the treatment of varicocele - Orhan, I; Onur, R; Semerciöz, A; Firdolas, F; Ardicoglu, A; Köksal, IT (Taylor & Francis Inc, 2005)
We reviewed records from patients who underwent two different microsurgical varicocelectomy methods: 147 (high inguinal (MHIV) and 65 sub-ingruinal (MSIV) microsurgery) to compare the therapeutic activity and complications. Patients who had 2 different microsurgical varicocelectomies were compared according to preoperative connected vein, number of designated arteries, postoperative semen and improvement degree in hormone parameters, increased ratio related with pregnancy and complications. The ratio of improvement of postoperative semen parameters in patients where MHIV and MSIV were performed was, 42% and 38% (p > 0.05). Pregnancy was achieved in MHIV at a ratio of 41% (34/82) and 33% (22/65) in MSIV (p > 0.05). There was no significant difference according to mean operation periods, the vein connected between the groups. The number of testicular arteries were significantly higher than the ones in MHIV (p < 0.01). However, as a postoperative complication, hydrocele was not seen in any of the patients, while relapses occurred in 1 MHIV and 2 MSIV patients. MHIV and MSIV techniques are effective methods to treat varicocele. However, the excess number of connected veins due to the anatomic feature of MSIV increases the possibility of relapses and the technical difficulty during surgical intervention.
Keywords: inguinal; male infertility; microsurgery; sub-inguinal; varicocele